Microfluidics-Based Single-Cell Research for Intercellular Interaction - Pang, Long; Ding, Jing; Liu, Xi-Xian; Kou, Zhixuan; Guo, Lulu; Xu, Xi; Fan, Shih-Kang (Frontiers in Cell and Developmental Biology, 2021)
Intercellular interaction between cell–cell and cell–ECM is critical to numerous biology and medical studies, such as stem cell differentiation, immunotherapy and tissue engineering. Traditional methods employed for delving into intercellular interaction are limited by expensive equipment and sophisticated procedures. Microfluidics technique is considered as one of the powerful measures capable of precisely capturing and manipulating cells and achieving low reagent consumption and high throughput with decidedly integrated functional components. Over the past few years, microfluidics-based systems for intercellular interaction study at a single-cell level have become frequently adopted. This review focuses on microfluidic single-cell studies for intercellular interaction in a 2D or 3D environment with a variety of cell manipulating techniques and applications. The challenges to be overcome are highlighted.